Innovative Nursing Practice: Emerging Technologies, Evidence-Based Interventions, and Future Directions in Patient-Centered Healthcare (International Journal of Pathology and Genetics of Disease and Nursing Management, 2026)
Innovative nursing practice has become an essential component of modern healthcare as hospitals and community health systems strive to improve patient outcomes, reduce healthcare costs, and enhance the quality and safety of care. The rapid advancement of digital health technologies, artificial intelligence, telemedicine, wearable monitoring devices, robotics, precision medicine, and clinical decision-support systems has significantly transformed the role of nurses in patient-centered healthcare delivery. Nurses are increasingly expected to integrate technological innovations with evidence-based interventions while maintaining compassionate, holistic, and ethical care. This review explores recent developments in innovative nursing practice and examines how emerging technologies influence clinical decision-making, patient engagement, disease prevention, chronic disease management, and interdisciplinary collaboration. Published literature from peer-reviewed journals, international clinical guidelines, and healthcare databases was critically evaluated to identify current trends, implementation strategies, barriers, and future opportunities. Evidence demonstrates that technological innovations improve medication safety, reduce clinical errors, facilitate early diagnosis, strengthen remote patient monitoring, and increase patient satisfaction when supported by appropriate education and organizational leadership. However, challenges, including limited digital literacy, financial constraints, data privacy concerns, workforce shortages, and unequal access to healthcare technologies, continue to impede widespread implementation. Successful adoption depends on continuous professional education, effective nursing leadership, supportive institutional policies, and interdisciplinary collaboration. Future nursing practice will increasingly rely on predictive analytics, personalized healthcare, virtual care models, and intelligent clinical systems while preserving the humanistic values that define nursing. Integrating technological innovation with evidence-based nursing practice offers substantial opportunities to strengthen healthcare quality, improve clinical outcomes, and promote equitable, patient-centered care across diverse healthcare settings. Continued research and investment in nursing innovation will remain essential for meeting evolving global healthcare needs and addressing future public health challenges.
Keywords: artificial intelligence; clinical decision support; digital health; evidence-based practice; innovative nursing; healthcare technology; patient-centered care; nursing informatics; nursing leadership; telehealth